Penerapan Program Urban Farming dalam Rangka Meningkatkan Kelestarian Lingkungan di Desa Ngaso, Kecamatan Ujung Batu - Dahlan Tampubolon; Ade Irawani; Alief Anugrah Bahari; Anisatul Khoiriyah; Erdian Masaputra; M. Gilang Mardiansyah; Naya Huwaidah; Sindi Antika; Sudira WaAgustiana Putri Harahap hyuni; Wandra Zuyandri (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
Community Service Program is a tangible expression of the student's obligation to perform one of the Tri Dharma of The College, which is in an aspect of devotion. Where this dedicated activity is carried out with the aim of solving problems and providing solutions to the real problems around people. Community Service Program is already underway in Ngaso Village, Ujung Batu Sub-District, Rokan Hulu Regency. The lack of awareness of people in the management of garbage is a major problem in the area, so it is a major concern for the ethics group. With these conditions, students are encouraged to develop programs that evisce "reuse" concepts on "Urban Farming" Urban Farming is an activity of raising crops by leveraging land with a finite method of verticulture. Where secondhand goods are used as containers for growing crops. The aim of the program is to exploit and reduce the amount of waste used bottles, to increase public awareness of the importance of preserving the environment, and to add aesthetic value to the target.